New records of Spelaeorhynchus praecursor Neumann, 1902 (Mesostigmata: Spelaeorhynchidae) in the Brazilian Caatinga - Bassini-Silva, Ricardo (2025)
The Neotropical bat-ectoparasite family Spelaeorhynchidae comprises seven species into in one genus. The species Spelaeorhynchus praecursor is the most distributed in the region, parasitizing phyllostomid bats of the subfamilies Carolliinae, Glossophaginae and Stenodermatinae. The present study expands the known geographic distribution of this species, providing new host records, as well as the first SEM images detailing the main characteristics of this species.